Analysis of potential hazards and risks of container loading and unloading activities on work at PT. Pelindo Multi Terminal - Mahendra, Hamzah; Zurairah, Masdania; Refiza (Jurnal VORTEKS, 2024)
HIRARC is a hazard identification, risk assessment, and risk control process, which identifies potential hazards in ordinary and unusual business activities, including an assessment of potential hazards and strategies to mitigate risks. Work accidents can occur due to actions, human conditions, and mechanical factors. The research method is data analysis in the work process and container filling, then risk control of each process. The data in the hazard and risk assessment is a qualitative analysis in AS/NZS 4360:2004. 53 sources of danger were identified from 12 stages of work. The results of the risk evaluation showed a low-risk level of 32% with 18 sources of danger, a moderate risk level of 28% with 16 sources of danger, a high-risk level of 16% with 9 sources of danger, and an extreme risk level of 24% with 14 sources of danger. This study concludes that in the dismantling process there are four stages of work, namely starting from the opening of the hatch (3 sources of danger), stevedoring (20 sources of danger), cargodoring (4 sources of danger), and delivery (2 sources of danger). In the loading process, there are four stages of work, starting from receiving (6 sources of danger), cargodoring (4 sources of danger).